Anode-free metal halide battery
Patent Information
- Application Number
- JP2024541822
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-21
- Filing Date
- 2023-01-06
- Publication Date
- 2025-02-28
Smart Images

Figure 2025505511000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates generally to the field of rechargeable batteries, and more specifically to anode-free metal halide rechargeable batteries. [Background technology]
[0002] Rechargeable batteries are used as power sources in a wide range of applications, such as industrial equipment, medical devices, electronics, electric vehicles, grid energy storage systems, etc. Battery technology is continually being developed to allow for higher energy densities and greater efficiency, which allows for the use of batteries as a power source for additional applications. Summary of the Invention
[0003] The disclosed embodiments include an anode-free metal halide battery. The metal halide battery includes a current collector, an electrolyte, and a cathode. The current collector includes a passivation layer of the insulating material. The passivation layer allows for metal ion transport. The electrolyte includes a solvent and at least one ion-conducting salt and is in contact with the current collector and the cathode. The cathode includes a metal halide salt incorporated in a conductive material. The anode-free metal halide battery may have several advantages over alternative designs. For example, compared to current lithium-ion batteries that use graphite cathodes, the disclosed anode-free metal halide batteries have higher energy density due to the weight and volume advantages of lithium compared to graphite. Additionally, these anode-free metal halide batteries can be manufactured more easily than solutions that use lithium metal cathodes, which require more modern manufacturing equipment to manage the sensitivity of lithium metal to air and moisture.
[0004] In some optional embodiments, the passivation layer includes an artificially formed ionically conductive material. The ionically conductive material may include, for example, polyvinyl alcohol (PVA) and / or polyethylene glycol (PEG). The inclusion of the ionically conductive passivation layer can improve the coulombic efficiency of the battery. Additionally, the ionically conductive passivation layer results in more stable battery performance over multiple cycles and increases the consistency of capacity retention during battery cycling.
[0005] An additional embodiment is directed to another anode-free metal halide battery. The metal halide battery includes a current collector, an electrolyte, and a cathode. The electrolyte includes a solid ion conductor and is in contact with the current collector and the cathode. The cathode includes a metal halide salt incorporated into a conductive material.
[0006] Further embodiments of the present disclosure include methods for forming an anode-free metal halide battery. The method includes forming a metal halide battery cell. The metal halide battery cell includes an anode current collector and does not include a separate metal anode. The method further includes applying a charging voltage to the metal halide battery cell to deposit metal ions on the anode current collector.
[0007] The above summary is not intended to describe each illustrated embodiment or every implementation of the present disclosure.
[0008] The drawings included in this disclosure are incorporated in and constitute a part of the specification. The drawings illustrate embodiments of the disclosure and, together with the detailed description, serve to explain the principles of the disclosure. The drawings are merely illustrative of typical embodiments and are not intended to limit the disclosure. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a diagram of an exemplary anode-free metal halide battery prior to initial charge, according to an embodiment of the present disclosure. [Diagram 2]FIG. 2 is a diagram of the exemplary anode-free metal halide battery of FIG. 1 after an initial charge, in accordance with an embodiment of the present disclosure. [Diagram 3] FIG. 3 is a diagram of the exemplary anode-free metal halide battery of FIG. 2 in a sealed cell, according to an embodiment of the present disclosure. [Figure 4] 1A-1D are scanning electron microscope (SEM) views of a conventional lithium ion anode current collector and a metal halide anode current collector constructed in accordance with an embodiment of the present disclosure. [Diagram 5] 1 is a graph showing initial charge and discharge curves for an anode-free battery cell including a lithium-ion intercalation cathode (solid line) and a metal halide anode (dotted line) according to an embodiment of the present disclosure. [Figure 6] FIG. 13 is a graph showing charge and discharge curves for two different anode-free metal halide batteries associated with uncoated SS current collectors (open squares) and polymer-coated SS current collectors (filled squares) in accordance with an embodiment of the disclosure. [Figure 7] FIG. 13 is a graph showing cycle performance data for two different anode-free metal halide batteries combined with uncoated SS current collectors (open circles) and polymer-coated SS current collectors (filled circles) in accordance with an embodiment of the disclosure. [Figure 8A] FIG. 13 shows a cross-sectional SEM image of an anode-free lithium iodide polymer-coated current collector after lithium deposition from an initial charge, according to an embodiment of the present disclosure. [Figure 8B] FIG. 8B is a magnified portion of the SEM image of FIG. 8A showing rounded lithium deposited on a current collector according to an embodiment of the present disclosure. [Figure 9] 1 is a graph showing charge and discharge curves for an anode-free metal halide battery having a Ni current collector, according to an embodiment of the present disclosure. [Figure 10] 1 is a graph showing cycle performance data for anode-free lithium iodide batteries combined with four different anode current collectors according to embodiments of the present disclosure. [Figure 11] 1 is a flow chart of an exemplary method for forming an anode-free metal halide battery cell according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] While the embodiments described herein are amenable to various modifications and alternative forms, details of which have been shown by way of example in the drawings and will be described in detail. It is to be understood, however, that the particular embodiments described are not to be taken in a limiting sense. On the contrary, the intention is to cover all modifications, equivalents and alternatives falling within the scope of the invention.
[0011] FIELD OF THE DISCLOSURE Aspects of the present disclosure relate generally to the field of rechargeable batteries, and more specifically to anode-free metal halide rechargeable batteries. The present disclosure is not necessarily limited to such applications, but various aspects of the disclosure may be understood through a consideration of various examples using this context.
[0012] Lithium-ion batteries are used in many applications, such as to power small power tools, electric vehicles, and to store energy for energy grid systems. As more applications for energy storage are developed, the demand for higher energy density batteries continues to grow, and intensive research and development from industry and academia has been conducted to meet the ever-increasing demands in terms of energy density and battery safety.
[0013] Current graphite anode-based lithium-ion batteries have inherent capacity limitations that limit the overall energy density of the battery. To overcome these limitations, the most common approach being actively researched is lithium metal-based batteries, because lithium metal has weight and volume advantages when applied as the anode. The main challenge to increase the energy density of such batteries is to form thinner lithium anodes to reduce the need for extra lithium sources and increase the volumetric energy density. However, the transition to practical Li metal-based batteries is not straightforward due to the inherent reactivity of lithium metal with electrolyte compounds and the inherent non-uniform plating of lithium ions. Another approach is to replace the conventional graphite anodes with flexible lithium metal anodes, but this requires modern manufacturing facilities with improved environmental control, as lithium metal is sensitive to air and moisture. The softness of lithium metal also creates significant challenges in management and manufacturing.
[0014] Recently, IBM® research team demonstrated a high-performance rechargeable metal halide battery using a lithium metal anode. These inventors reported that the metal halide battery has the formation of a stable anode protection layer, which can help to enhance fast charging performance and long-term battery operation. To further improve the gravimetric and volumetric energy density of this metal halide battery while eliminating the concerns associated with the sensitive metal anodes discussed above, a new type of rechargeable metal halide battery that does not use a separate metal anode is disclosed herein. This anode-free metal halide battery can reduce side reactions from the highly reactive lithium metal and provide uniform lithium ion plating upon cycling. Furthermore, the disclosed anode-free metal halide battery can have a higher energy density than conventional batteries.
[0015]
[0004] Embodiments of the present disclosure are directed to a new type of rechargeable metal halide battery. In particular, some embodiments of the present disclosure include a conductive current collector at the negative electrode, an electrolyte, and a cathode. The cathode includes a metal halide and a conductive material.
[0016] Unlike conventional batteries, the disclosed battery does not require any metal anode in the initial cell assembly. Instead, the metal halide cathode contains metal ions that can be deposited on the conductive current collector at the negative electrode in the first charging step. These deposited metals then act as the anode active material and participate in the successive electrochemical reactions in the cycle. The use of unique surface protection species of the metal halide battery system allows for uniform metal ion plating and stripping even on the current collector, which allows for stable operation of the battery. Furthermore, since the embodiments of the present disclosure do not use sensitive metal anodes (e.g., lithium foils), the cell manufacturing process can be significantly simplified without any concerns associated with handling flexible metal foils (e.g., dents, wrinkles, etc.) or controlling undesirable side reactions of the metal. Furthermore, the anode-free metal halide battery disclosed herein can inhibit lithium dendrite formation, thereby preventing short circuits while retaining the improved energy density of the battery cell.
[0017] It should be understood that the aforementioned advantages are exemplary advantages and should not be construed as limiting, and embodiments of the present disclosure may include all, some, or none of the aforementioned advantages while remaining within the scope of the present disclosure.
[0018] Referring now to the drawings, FIG. 1 illustrates a diagram of an exemplary anode-free metal halide battery 100 prior to an initial charge, according to an embodiment of the present disclosure. As used herein, "anode-free" means that the battery 100 in its initial configuration (i.e., prior to an initial or first charge) does not include a lithium anode. The battery 100 includes a current collector 102, a protective coating 104 formed on the top side of the current collector 102, an electrolyte 106, and a cathode 108. Additionally, the battery 100 includes a separator 110. In some embodiments, as discussed herein, the battery 100 may not include the separator 110 or the protective coating 104, or both. The battery 100 operates via reduction-oxidation (redox) reactions, utilizing different oxidation states and redox reactions of one or more components or elements for charging and discharging. It should be understood that the drawings are not necessarily drawn to scale to facilitate visualization of each component separately. For example, the protective coating 104 may be substantially thinner than depicted in the figures.
[0019] In some embodiments, the current collector 102 is a metal, suitable examples include, but are not limited to, stainless steel, nickel, and mixtures and combinations thereof. In this application, components made of a particular material may, in some cases, contain incidental impurities.
[0020] In some embodiments, the protective coating 104 is any suitable coating that is conductive to lithium ions. In other words, the protective coating 104 allows lithium ions to pass through it. The protective coating can be a naturally formed passivation layer called a solid electrolyte interface layer (SEI) or a polymer coating artificially applied to the current collector 102 (artificial SEI). Exemplary polymers that may be used include, but are not limited to, polyvinyl alcohol (PVA), poly(ethylene glycol), poly(propylene glycol), polycarbonate, polyester, polyethylene oxide (PEO), polyurethane (PU), styrene butadiene rubber (SBR), polyvinylidene fluoride (PVDF), poly(tetrafluoroethylene) (PTFE), and a combination of poly(ethylene glycol) (PEG) copolymerized with polyhedral cage silsesquioxane (POSS), also referred to as PEG-POSS. The protective coating 104 can be a single ion conductor or a polyelectrolyte, including polymers with sulfonic acid groups, carboxylic acid groups, and phosphonic acid groups, or any strong acid groups attached to a polymer matrix in the form of a lithium salt. In some embodiments, the protective coating 104 can include inorganic metal oxides and / or metal sulfides. In some embodiments, the thickness of the protective coating 104 is about 20 μm, and the coating layer includes a UV crosslinked polymer. In some embodiments, the protective coating 104 is electrically insulating in addition to being lithium ion conductive. This helps to prevent electrons from flowing through the electrolyte 106 while still allowing lithium ions to pass through and deposit on the current collector 102.
[0021] The electrolyte 106, which may be aqueous or non-aqueous, includes a solvent and at least one ionically conductive salt that dissociates into respective metal ions and respective counter anions. In some non-limiting examples, the metal ions include at least one of Li, Mg, Zn, Al, and Na, and the counter anion is nitric acid (NO 3 -), hexafluorophosphate (PF 6 - ), tetrafluoroboric acid (BF 4 - ), Bis(oxalato)boric acid (BOB - ), difluorooxalatoboric acid (DFOB - ), trifluoromethanesulfonic acid (TF - ), and trifluorosulfonyl imide (TFSI - )
[0022] In some embodiments, the electrolyte 106 is a solid electrolyte that includes an ionically conductive material. The electrolyte 106 may also be electrically insulating. For example, the electrolyte 106 may be a solid polymer electrolyte (SPE), an inorganic solid electrolyte (ISE such as ceramic), or a composite polymer electrolyte (CPE). In some embodiments, the ionically conductive protective coating 104, which may be a polymer, may function as a solid electrolyte.
[0023] In some embodiments, the electrolyte 106 also includes any metal halide (e.g., MXn, where M is a metal, X is a halogen, and n is an integer greater than 0). In some examples, the metal halide is an electrolyte salt that dissociates into a respective halide ion and a respective metal ion. For example, the metal halide may dissolve in a solvent that includes a heterocyclic compound and dissociate into a respective metal and halide ion. In some examples, the halide ion may include at least one ion of I, Br, Cl, or F (e.g., X may be I, Br, Cl, or F), and the metal ion may include at least one ion of Li, Mg, Zn, Al, or Na (e.g., M may be Li, Mg, Zn, Al, or Na). In other examples, the metal halide may include elements other than I, Br, Cl, F, Li, Mg, Zn, or Na, or combinations thereof. In some embodiments, the metal halide may provide the electrolyte 106 with additional ionic conductivity.
[0024] In various embodiments, the electrolyte 106 includes one or more solvents capable of transporting metal ions and counterions. In various non-limiting embodiments, suitable solvents may be selected from non-aqueous organic solvents, such as ethers, glymes, carbonates, nitriles, amides, amines, organosulfur solvents, organophosphate solvents, organosilicon solvents, fluorinated solvents, adiponitrile (ADN), propylene carbonate (PC), dimethoxyethane (DME), and mixtures and combinations thereof.
[0025] In some examples, one or more additional solvents may be included in the electrolyte 106 to further improve the electrochemical performance of the battery 100, such as by enhancing rechargeability, cyclability, or the like.
[0026] In some non-limiting embodiments, the solvent in electrolyte 106 includes any heterocyclic compound, which is referred to herein as an aromatic or non-aromatic cyclic compound having atoms of at least two different elements as ring members. A cyclic compound (ring compound), as used herein, refers to a compound in which one or more series of atoms in the compound are connected to form a ring. In various embodiments, suitable cyclic compounds for electrolyte 106 include five-membered rings such as pyrrolidine, oxolane, thiolane, pyrrole, furan, and thiophene, six-membered rings such as piperazine, oxane, thiane, pyridine, pyran, and thiopyran, and seven-membered rings such as azepane, oxepane, thiepane, azepine, oxepine, and thiepene. Examples of suitable heterocyclic compounds include, but are not limited to, tetrahydrofuran, tetrahydropyran, tetrahydrothiophene, oxathiolane, succinimide, oxazolidone, γ-butyrolactone, γ-caprolactone, ε-caprolactone, γ-valerolactone, pyrrolidine, imidazolidine, sulfolane, thiane, dioxolane, and mixtures and combinations thereof. In some embodiments, suitable heterocyclic compounds include, but are not limited to, cyclic ethers, cyclic esters, and mixtures and combinations thereof.
[0027] In some examples, the electrolyte 106 includes a solvent containing a heterocyclic compound and one or more additional solvents in substantially equal proportions.
[0028] In another non-limiting embodiment, the solvent in the electrolyte 106 includes any nitrile compound. The nitrile compound has a chemical formula of N≡CR or N≡CRC≡N, where R is an organic functional group. Examples of organic functional groups for the nitrile compound include ether, alkyl ether, thioether, alkyl thioether, or the like. In some non-limiting examples, the nitrile compound is selected from valeronitrile, nonanenitrile, hexanenitrile, acetonitrile, propionitrile, glutaronitrile, methoxyacetonitrile (MAN), methoxybenzonitrile, methoxypropionitrile (e.g., 3-methoxypropionitrile (MPN)), methylglutaronitrile, butoxypropionitrile, butoxybenzonitrile, and mixtures and combinations thereof. In some examples, the nitrile compound in the electrolyte 106 may improve electrochemical performance (e.g., reversibility, rechargeability, or cyclability, or a combination thereof), produce less irreversible carbonate by-products, or improve power density.
[0029] In some examples, the electrolyte 106 includes equal proportions of a solvent that includes a nitrile compound and one or more additional solvents.
[0030] The electrolyte 106 includes an oxidizing gas. In some examples, the electrolyte 106 may be in the presence of an oxidizing gas, and the phrase "including an oxidizing gas" is intended to include such configurations. In some examples, the oxidizing gas may be dissolved in a solvent that includes the electrolyte 106. In some non-limiting examples, the oxidizing gas includes at least one of oxygen, air, nitric oxide, or nitrogen dioxide. The oxidizing gas, as described above, helps induce redox reactions in the battery 100 and helps achieve highly reversible redox reactions, which can contribute to improved electrochemical performance of the battery 100. The oxidizing gas helps induce such redox reactions and can contribute to the integration and stabilization of the solid electrolyte interface (SEI) layers in the electrodes (i.e., the current collector 102 and the cathode 108), but does not participate in the capacity-generating redox reactions of the battery 100. In some examples, an electrolyte lacking an oxidizing gas may exhibit little or no rechargeability.
[0031] In the embodiment described below with respect to experimental results and examples, the electrolyte 106 is about 0.2 M LiNO in dioxolane (DOL). 3 and a mixture of approximately 0.5 M LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), which also contains 1,2-dimethoxyethane (DME).
[0032] During charging of the battery 100, the cathode 108 releases electrons through a redox reaction of the metal halide and provides a conductive path to the external electrical circuit to which the battery 100 is connected, while metal ions diffuse from the cathode through the electrolyte 106 to the current collector and are reduced to metal on the current collector at the negative electrode by accepting electrons transferred from the external circuit. Similarly, during discharging of the battery 100, the deposited lithium metal is oxidized to lithium ions and a cathode redox reaction occurs at the cathode 108 by releasing electrons through the external electrical circuit to which the battery 100 is connected and accepting electrons transferred from the external electrical circuit.
[0033] Cathode 108 includes a conductive material and a metal halide salt incorporated or applied to the conductive material. In various embodiments, the total amount of metal halide in cathode 108 is greater than the total amount of metal halide in electrolyte 106, or is at least two, three, or five times the total amount of metal halide in electrolyte 106.
[0034] In some examples, not intended to be limiting, the conductive material in the cathode 108 may include conductive powders independently selected from metal or carbon powder or both, woven or non-woven metal fibers, metal foam, woven or non-woven carbon fibers, or the like. Additionally or alternatively, the cathode 108 may include stainless steel mesh, aluminum (Al) mesh, nickel (Ni) foam, carbon cloth, or carbon paper, or combinations thereof. For example, in one embodiment, the cathode 108 may include stainless steel mesh with carbon nanoparticles deposited thereon.
[0035] In another embodiment, the cathode 108 may be an electrically conductive porous material. In some embodiments, the cathode 108 may include a carbon material selected from an amorphous carbon material, a crystalline carbon material, and mixtures and combinations thereof. Suitable amorphous carbon materials include, but are not limited to, carbon black and porous vitreous carbon particles, and mixtures and combinations thereof. In some embodiments, crystalline carbon materials include, but are not limited to, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, and mixtures and combinations thereof.
[0036] In some embodiments, the cathode 108 may be, for example, a lithium cobalt oxide (LCO, e.g., LiCoO 2 ), lithium nickel cobalt aluminum oxide (NCA, e.g., LiNi x Co y Al z O 2 , LiNi 0.8Co 0.15 Al 0.05 O 2 ), lithium-ion manganese oxide (LMO, e.g., LiMn 2 O 4 ), lithium nickel manganese cobalt oxide (NMC, e.g., LiNiMnCoO 2 ), nickel cobalt manganese (NCM, e.g., LiNi x Co y Mn z O 2 , LiNi0 .33 Co 0.33 Mn 0.33 O 2 ), or lithium iron phosphate (LFP, e.g., LiFePO 4 ), as well as mixtures and combinations thereof.
[0037] The cathode 108 includes at least one metal halide salt MXn, where M is a metal, X is a halide, and n is an integer greater than 0 (e.g., 1 to 3). In some examples, the metal halide is I - , Br - , Cl - , or F - (e.g., X can be I, Br, Cl, or F), and the metal ion is Li + , Mg 2+ , Zn 2+ , Al 3+ , or Na + (For example, M can be Li, Mg, Zn, Al, or Na.) In other examples, the metal halide can include elements other than I, Br, Cl, F, Li, Mg, Zn, Al, or Na, or combinations thereof.
[0038] In some embodiments, cathode 108 may optionally include a polymeric binder. Suitable polymeric binders can vary widely, examples of which include, but are not limited to, poly(tetrafluoroethylene) (PTFE), polyvinylidene fluoride (PVDF), or sulfonated tetrafluoroethylene-based fluoropolymer-copolymers sold under the trademark NAFION by DowDuPont (Midland, Mich.), and mixtures and combinations thereof.
[0039] In some embodiments, the cathode optionally comprises a diatomic halogen molecule. Suitable diatomic halogen molecules include I 2 , Br 2 , Cl 2 , F 2 Includes 。
[0040] In various embodiments, the cathode 108 includes about 25 wt% conductive material, about 70 wt% metal halide salt, and about 5 wt% optional polymeric binder, based on the total weight of the cathode 108. For example, in some embodiments, the cathode 108 includes about 50 wt% to about 80 wt%, or about 40 wt% to about 90 wt%, or about 30 wt% to about 100 wt%, or about 10 wt% to about 100 wt% metal halide, based on the total weight of the cathode 108.
[0041] In various embodiments, the metal halide in the cathode 108 may be interspersed or dispersed throughout the matrix of the conductive material and any polymeric binder present. In some embodiments, the conductive material itself may be a porous material and the metal halide salt may be disposed in pores therein. In some embodiments, the metal halide may be adsorbed onto the conductive material and / or the polymeric binder in addition to being disposed in the pores. In some embodiments, the metal halide may be concentrated near a major surface of the cathode to form a gradient in the conductive matrix material or to form one or more metal halide rich layers.
[0042] In the embodiment described below with respect to experimental results and examples, the cathode 108 comprises lithium iodide deposited on a porous carbon cathode (LiI-carbon composite cathode). The porous carbon cathode comprises activated carbon (hosting material), Super P (electronic conductor), and styrene butadiene rubber / carboxymethyl cellulose (SBR / CMC) binder, which were prepared by coating a slurry of a 85 / 15 weight ratio carbon / binder mixture in alcohol onto a stainless steel current collector. The active cathode material, LiI in methanol, was compounded separately and applied onto the carbon cathode to form the LiI-carbon composite cathode. The LiI-carbon composite cathode was then dried on a hot plate at 120° C. for about 12 hours. All dosing and drying steps were carried out in an Ar-filled glove box.
[0043] In some examples, the battery 100 includes an optional separator 110. The separator 110 forces electrons to pass to an external electrical circuit to which the battery 100 is connected, so that electrons do not flow through the battery 100 (e.g., through the electrolyte 106 of the battery 100) while still allowing metal ions to flow through the electrolyte 106 of the battery 100 during charging and discharging. In some examples, the separator 110 can be saturated with, immersed in, surrounded by the electrolyte 106, or the like. The separator 110 can include a non-conductive material to prevent the movement of electrons through the battery 100, so that the electrons move instead through the battery terminals and through the external circuit. For example, the separator 110 can include glass, non-woven fibers, polymeric films, rubber, or the like. In the embodiment described below with respect to experimental results and examples, the separator 110 is a Celgard® 2325 separator disposed between the cathode and the anode.
[0044] In some examples, the battery 100 has a closed or substantially closed volume. For example, the current collector 102, protective coating 104, electrolyte 106, cathode 108, and separator 110 may be in a closed or substantially closed cell or other enclosure. In this manner, the oxidizing gas of the electrolyte 106 remains within the battery 100, so that the battery 100 has a relatively fast charge rate, high energy efficiency, high power density, high reversibility, high cyclability, or any combination thereof, as described herein.
[0045] Referring now to FIG. 2, a diagram of the exemplary anode-free metal halide battery 100 of FIG. 1 after initial charging is shown, according to an embodiment of the present disclosure. As shown in FIG. 2, the battery 100 is substantially the same as that shown in FIG. 1, except that the initial charging of the battery 100 reduces the lithium ions and plates metallic lithium 202 onto the current collector 102. In other words, charging the battery 100 causes the lithium ions initially present in the cathode 108 to pass through the electrolyte 106, permeate the protective coating 104, and then plate the top of the current collector 102 in the form of metallic lithium 202 by accepting electrons transferred through the external circuit and the current collector. The metallic lithium 202 can effectively act as an anode for the battery 100 during subsequent operation. In other words, the metallic lithium 202 can take up metal ions from the electrolyte 106 during charging and release metal ions to the electrolyte 106 during discharging. In this manner, the battery 100 can be fabricated without a separate anode (eg, without a lithium foil anode), which can then be formed through deposition of lithium 202 on the current collector 102 during an initial charge.
[0046] Battery 100 is capable of many charge and discharge cycles (e.g., exhibits good rechargeability) even at relatively high charging current densities. In some examples, battery 100 has a current density of about 1 mA / cm 2 , about 5mA / cm 2 , about 10mA / cm 2 , or about 20mA / cm2 At or above this current density, the battery 100 can complete at least 100 charge and discharge cycles. 2 , about 5mA / cm 2 , about 10mA / cm 2 , or about 20mA / cm 2 At the above current density, at least 1000 charge and discharge cycles can be completed.
[0047] Additionally, or alternatively, the battery 100 may exhibit relatively high energy efficiency. For example, the battery 100 may exhibit a current density of about 1 mA / cm 2 , about 5mA / cm 2 , about 10mA / cm 2 , or about 20mA / cm 2 In some examples, the battery 100 may exhibit energy efficiencies of 90% or greater at current densities of about 1 mA / cm. 2 , about 5mA / cm 2 , about 10mA / cm 2 , or about 20mA / cm 2 At current densities above this, it is possible to achieve an energy efficiency of 99% or more.
[0048] Referring now to FIG. 3, a diagram of the exemplary anode-free metal halide battery 100 of FIG. 2 within an enclosed cell 300 is shown, according to an embodiment of the present disclosure. The enclosed cell 300 may include a cell that houses the battery 100 during operation of the battery 100, a cell used to manufacture the battery 100, or both. For example, the enclosed cell 300 may include a cell sold under the trade name SWAGELOK by Swagelok of Solon, Ohio, and may be used to manufacture the battery 100. In some examples, the enclosed cell 300 may include an inlet tube 302 or an outlet tube 304, or both. The inlet tube 302 and the outlet tube 304 may be used to introduce and remove air or other gases, such as oxidizing gases of the electrolyte 106, into and from the enclosed cell.
[0049] In one exemplary embodiment, to manufacture the cathode 108, powders of conductive material, metal halide, lithium ions, and any optional polymeric binder are simply mixed to form a slurry. In some embodiments, any solvent may be used to adequately disperse the powder. The slurry is then provided on the surface of a separator 110 or any type of mesh, which may be referred to herein as a gas diffusion layer (GDL), and dried to form the cathode 108. In another embodiment, the slurry is provided on the surface of any current collector in the cathode (e.g., metal foil). In various non-limiting embodiments, the slurry may be air dried, dried in an oven, or a combination thereof.
[0050] In some instances, the metal halide itself may be dried prior to incorporation into the slurry. In one non-limiting example, the metal halide may be dried on a hot plate in an argon-filled glove box at about 120° C. for greater than 12 hours.
[0051] To form a battery cell, the current collector 102 and optional separator 110 with the cathode 108 formed thereon can be stacked together. In some embodiments, the optional separator 110 is saturated with an electrolyte solution 106, or an electrolyte solution 106 is disposed in the cell between the current collector 102 and the cathode 108, or both. After the current collector 102, saturated separator 110, and cathode 108 are stacked, the sealed cell 300 can be closed or substantially closed to form a closed or substantially closed volume around the stack.
[0052] An oxidizing gas is then introduced into the sealed cell 300 to produce the battery 100. In some examples, introducing the oxidizing gas into the sealed cell 300 includes introducing the oxidizing gas into the sealed cell 300 via the inlet tube 302. In some examples, the sealed cell 300 may include or be in the presence of an inert gas, such as argon, prior to introducing the oxidizing gas into the sealed cell 300. In such examples, the introduction of the oxidizing gas may purge the inert gas in the sealed cell 300 with the oxidizing gas and completely replace it with the oxidizing gas. For example, the oxidizing gas may be introduced into the sealed cell 300 via the inlet tube 302 and the inert gas may be purged through the outlet tube 304. In some examples, the concentration of the oxidizing gas in the sealed cell 300 may be about 5 wt% to about 100 wt%, about 20 wt% to about 100 wt%, about 50 wt% to about 100 wt%, or about 80 wt% to about 100 wt% of the total amount of gas in the sealed cell 300 (e.g., compared to the total amount of the oxidizing gas and the inert gas in the sealed cell 300).
[0053] The present disclosure will now be described with reference to several non-limiting examples with reference to Figures 4-10. In particular, Figures 4-10, which show images and result data collected from a number of examples studied by the inventors of the present disclosure, will be described first, followed by a detailed description of the experiments that produced the data shown in Figures 4-10. However, it should be understood in advance that these examples are illustrative examples only and are not intended to be limiting. As will be recognized by those skilled in the art, many modifications may be made to the specific examples without departing from the scope of the invention, and such modifications are contemplated by the present disclosure. For example, alternative materials, material compositions, and material arrangements that are not otherwise inconsistent with the present disclosure are contemplated.
[0054] In particular, Figures 4 and 5 compare two different anode-free batteries, one with a conventional lithium-ion cathode and the other with a metal halide cathode constructed according to an embodiment of the present disclosure. Referring now to Figure 4, scanning electron microscope (SEM) images 400, 450 of lithium-deposited current collectors from an anode-free battery cell (400) with a conventional lithium-ion cathode and an anode-free battery cell (450) with a metal halide cathode constructed according to an embodiment of the present disclosure are shown. In particular, the SEM images 400, 450 show lithium plating behavior that has a very strong effect on the electrochemical performance, such as the rate capability and long-term cycle life, of the lithium battery. In Figure 4, stainless steel (SS) current collectors were used for the anode-free lithium-ion battery and the anode-free metal halide battery because the commonly used aluminum and copper current collectors tend to corrode in halide ion containing electrolytes.
[0055] As shown in Figure 4, the Li plating behavior is significantly different between the two battery chemistries. In particular, the lithium plating of the metal halide cathode is more uniform, due to the relatively uniform current distribution, which allows for better stripping and plating during cycling. This is shown by the large grain-like deposits of lithium 452 shown in the second SEM image 450 in Figure 4. In contrast, the SEM image 400 of the lithium deposits produced by the lithium-ion cathode cell shows needle-like lithium dendrites 402. These dendrites 402 tend to form dead lithium pieces during cycling, which can significantly reduce the overall capacity of the cell. Sharp dendrites can also short the battery, resulting in cell failure. Thus, Figure 4 shows that the metal halide battery chemistry results in more uniform lithium plating onto the stainless steel current collector.
[0056] As explained, the form of lithium affects the cycling efficiency of the battery. The resulting initial charge and discharge curves for the anode-free battery of Figure 4 are shown in Figure 5. In particular, Figure 5 is a graph 500 showing the initial charge 502, 504 and discharge 506, 508 for an anode-free lithium ion battery (502, 506) and for an anode-free metal halide battery (504, 508) constructed according to embodiments of the present disclosure, with the capacity cut off below 0.5 mAh.
[0057] As shown in graph 500, under the operating voltage, the anode-free lithium ion battery has a coulombic efficiency (CE) of 49%. In contrast, the anode-free metal halide battery shows a coulombic efficiency of 73%, which means that uniform lithium plating is closely related to higher lithium stripping in the battery. In other words, the discharge curve 506 for the lithium ion battery drops (shows a rapid drop in voltage) at about 0.25 mAh capacity, which is about 49% of the 0.5 mAh the battery was charged to, as shown by the charge curve 502. In contrast, the discharge curve 508 for the SS metal halide cathode battery shows a voltage drop point at about 0.365 mAh, or about 73% of the 0.5 mAh the battery was filled to, as shown by the charge curve 504. This also indicates that the anode-free metal halide battery has more promising results compared to the anode-free lithium-ion battery cell, which is likely a result of the stable and uniform SEI layer formed on the current collector.
[0058] Figures 6 and 7 compare the characteristics of an anode-free metal halide battery with a bare metal stainless steel current collector to an anode-free metal halide battery with an artificial SEI (polymer-based protective coating) on the top side of the stainless steel current collector. UV-crosslinked polyethylene glycol reinforced with cage-type silsesquioxane (POSS-PEG) was used as the artificial SEI layer. As shown in Figure 5, the anode-free metal halide battery charges and discharges properly with relatively high coulombic efficiency. Along with the morphological benefits of lithium plating from the identified metal halide cathode, the addition of an artificial protective layer to the current collector can help prevent active material loss due to SEI formation and produce higher capacity and cycle life. For this reason, a lithium ion conducting polymer coating is applied to the current collector, which is used in conjunction with the current collector and lithium deposit as the anode for the battery. In some embodiments, the thickness of the polymer coating is about 20 μm, and the coating layer is polymerized by UV light.
[0059] The aged charge and discharge curves obtained from an anode-free metal halide cell with a stainless steel (SS) current collector are shown in Figure 6. In particular, Figure 6 is a graph 600 showing the charge 602, 604 and discharge 606, 608 curves for a metal halide cell using a bare metal (in this case, stainless steel) current collector (604, 608) and for a metal halide cell including a polymer coating on top of the stainless steel current collector (602, 606). Below capacity cutoff, the polymer coated SS cell exhibits higher discharge capacity and coulombic efficiency (as shown by discharge curve 606) compared to the bare SS cell (as shown by discharge curve 608).
[0060] FIG. 6 further shows that in terms of overvoltages during charge and discharge reactions, the charge overvoltage of the polymer-coated SS cell is higher than that of the bare SS cell due to the thick polymer coating. This is shown by the charge curve 602 of the polymer-coated SS cell exceeding the charge curve 604 of the bare metal SS cell. Similarly, the discharge overvoltage of the polymer-coated SS cell is higher, indicating that the lithium ion conducting polymer coating has a resistance for lithium ions stripping from the anode. The resistance induced by the ion conducting polymer coating may be reduced by increasing the ionic conductivity or by reducing the thickness of the polymer coating, or both.
[0061] Referring now to FIG. 7, a graph 700 is shown illustrating cycling performance data for two different anode-free metal halide battery cells according to an embodiment of the present disclosure. As can be seen in graph 700, the polymer-coated SS cell has higher capacity and stable cyclability after an initial stabilization cycle. In contrast, the bare SS cell has slightly unstable cycling for 40 cycles. This indicates that the engineered polymer coating increases the consistency of charge capacity in the anode-free metal halide battery over repeated cycling.
[0062] Figures 8A and 8B show SEM images 800, 850 of a polymer-coated current collector obtained from an anode-free metal halide battery cell after lithium deposition from an initial charge according to an embodiment of the present disclosure. In particular, Figure 8B shows a magnified portion 850 of the SEM image 800 of Figure 8A. Figures 8A and 8B were generated using a capacity cutoff of 0.1 mAh for the battery cell.
[0063] 8A and 8B show a stainless steel current collector 802 on which a polymer 804 has been deposited. During the initial charging operation, lithium ions penetrated the polymer 804 and were deposited on the current collector 802 as lithium metal 806. The lithium metal 806 is deposited substantially uniformly on the underside of the polymer 804 and on the topside of the current collector 802. This indicates that the polymer layer is a lithium ion conductor and that the charging reaction occurs properly under this artificial polymer SEI layer. The enlarged view in FIG. 8B further shows the rounded lithium deposits 806, which are uniformly arranged on the current collector, in contrast to the needle-like dendrites formed on the anode-free metal halide battery cell. Thus, it is possible to operate the lithium anode-free metal halide battery reversibly.
[0064] Figures 9 and 10 show the electrochemical characteristics of anode-free lithium iodide cells assembled with different current collectors and artificial SEI layers (e.g., bare metal or polymer-coated). For these experiments, anode-free lithium iodide battery cells were assembled in a dry air atmosphere, Ni and SS foils were used as anode current collectors, and polyvinyl alcohol was applied onto the current collectors as an artificial SEI layer.
[0065] 9, a graph 900 is shown illustrating charge 902 and discharge 904 curves for an anode-free lithium iodide battery cell assembled with a PVA-coated Ni substrate according to an embodiment of the present disclosure. The charge and discharge performance was evaluated under voltage cutoff conditions of 2.0 V to 3.5 V. It shows a higher coulombic efficiency (CE) of over 80% and good charge and discharge behavior without any voltage spikes.
[0066] Furthermore, the results show that the anode-free metal halide battery disclosed herein can operate in a dry air atmosphere similar to the cell operated in a pure oxygen atmosphere as shown in FIG. 6. Notably, when the battery cell is tested in an oxygen atmosphere, the lower voltage was limited by the 2.6 V cutoff in FIG. 6 due to the oxygen reduction reaction occurring near 2.5 V. However, when the same battery cell is tested in dry air, the battery cell voltage can be extended up to 2.0 V (FIG. 9), which allows for a higher battery cell capacity.
[0067] Referring now to FIG. 10, a graph 100 is shown illustrating cycling performance data for four different anode-free lithium iodide battery cells assembled with bare SS (grey squares) and bare Ni (black circles) current collectors, as well as using PVA-coated SS (grey diamonds) and PVA-coated Ni (black triangles), according to an embodiment of the present disclosure. The cycling performance data was obtained under dry air atmosphere at 0.3C. As shown in the graph 1000, the cells with Ni current collectors have higher capacity retention throughout the cycles compared to those with SS current collectors. Also, in terms of cycle number, the cells with SS current collectors have shorter cycle life than the cells with Ni current collectors. In the case of Ni substrates, applying a PVA coating on the substrate enhances cycling stability up to 30 cycles under dry air atmosphere. As shown, using Ni foil as the current collector and a PVA coating as the artificial SEI layer further enhances the electrochemical performance of the anode-free metal halide cells.
[0068] 11, a flow chart of an exemplary method for forming an anode-free metal halide battery cell according to an embodiment of the present disclosure is shown. Method 1100 may be performed by hardware, firmware, software running on a processor, or any combination thereof. For example, method 1100 may be performed by a computer system (e.g., having a processor and memory) configured to control a robot or other device or both to assemble a battery. Method 1100 may begin at operation 1102, where an anode-free battery cell assembly is formed.
[0069] As disclosed herein, the anode-free battery cell assembly includes a cathode, a separator, an electrolyte, and a current collector for one or both electrodes. The anode-free metal halide batteries demonstrated in this disclosure do not include a lithium anode in the initial cell, but only an anode current collector. Instead, the cathode may consist of a lithium-containing active cathode material deposited on a porous cathode (e.g., a carbon cathode such as a LiI-carbon composite cathode). In some embodiments, a passivation layer, also known as a solid electrolyte interphase, is formed on the top side of the current collector in the negative electrode. In other embodiments, a polymer coating (artificial SEI) is deposited on the top side of the current collector in the negative electrode.
[0070] In some embodiments, the porous carbon cathode includes activated carbon (hosting material), Super P (electronic conductor), and styrene butadiene rubber / carboxymethyl cellulose (SBR / CMC) binder, which were prepared by coating a slurry of the carbon / binder mixture in alcohol at an 85 / 15 weight ratio onto a stainless steel current collector. The active cathode material, LiI in methanol, was prepared separately and dosed onto the carbon cathode to form a LiI-carbon composite cathode. The LiI-carbon composite cathode was then dried on a hot plate at 120 °C for about 12 h, and all dosing and drying steps were performed in an Ar-filled glove box.
[0071] In some embodiments, the electrolyte is about 0.2 M LiNO in dioxolane (DOL). 3 and about 0.5 M LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), which also contains 1,2-dimethoxyethane (DME). The separator may be, for example, a Celgard® 2325 separator, and may be disposed between the cathode and the current collector.
[0072] To form an anode-free battery cell assembly, the current collector and optional separator with the cathode formed thereon may be stacked. In some embodiments, the optional separator is saturated with an electrolyte solution, or an electrolyte solution is disposed in the cell between the current collector and the cathode, or both. After the current collector, saturated separator, and cathode are stacked, the battery cell may be closed or substantially closed to form a closed or substantially closed volume around the stack.
[0073] An oxidizing gas may then be introduced into the sealed cell to produce the battery 100. In some examples, introducing the oxidizing gas into the sealed cell includes introducing the oxidizing gas into the sealed cell through an inlet tube. In some examples, the sealed cell may include or be in the presence of an inert gas, such as argon, prior to introducing the oxidizing gas into the sealed cell. In such examples, the introduction of the oxidizing gas may purge the inert gas in the sealed cell with the oxidizing gas and completely replace it with the oxidizing gas. For example, the oxidizing gas may be introduced into the sealed cell through an inlet tube and the inert gas may be purged through an outlet tube. In some examples, the concentration of the oxidizing gas in the sealed cell 300 may be between about 5 wt% and about 100 wt%, between about 20 wt% and about 100 wt%, between about 50 wt% and about 100 wt%, or between about 80 wt% and about 100 wt% of the total amount of gas in the sealed cell.
[0074] After forming the anode-free battery cell assembly, a charging voltage may be applied to the cell assembly in operation 1104. The application of the voltage causes lithium ions, electrolyte, or both, which may initially be present in the cathode, to migrate toward the current collector and deposit on the top side of the current collector as metallic lithium, which acts as the anode. In embodiments including a naturally formed passivation layer (SEI layer) on a bare metal current collector, the lithium ions may pass through the passivation layer and deposit on the top side of the bare metal current collector, forming a metallic lithium layer that functions as the anode for the resulting battery. In embodiments having a polymer-coated current collector, the polymer coating may function as an artificial SEI. In these embodiments, the lithium ions may permeate the polymer coating and deposit on the top side of the current collector, forming a metallic lithium layer. As a result of the lithium being deposited on the current collector, the current collector, along with the lithium deposits and polymer coating, may essentially convert into and function as an anode for the battery. After the initial charging voltage has been applied for a sufficient time to allow migration of lithium ions to the current collector, method 1100 may end.
[0075] We now describe in detail several exemplary embodiments of anode-free metal halide batteries, which are non-limiting examples that the inventors have successfully constructed and tested using the methods disclosed herein.
[0076] Example 1: An anode-free metal halide cell assembled with a LiI-carbon composite cathode and a stainless steel (SS) current collector was operated under oxygen and dry air.
[0077] Following the general procedure for anode-free metal halide cells described above, the cells were assembled in an Ar-filled glove box or a glove box filled with dry air. For SEM analysis, the SS-LiI / C composite cell was assembled in a Swagelok cell in an Ar-filled glove box, and oxygen gas was bubbled into the assembled cell for 30 s. The cell was then started to operate under oxygen atmosphere after closing the inlet / outlet valves. After the first charge to 1 mAh, the cell was disassembled, and the SS current collector was carefully rinsed with DOL / DME solvent mixture and then dried under vacuum at room temperature. As shown in Figure 4 (right figure), smooth and uniform lithium deposits were observed on the SS current collector. The SS-LiI / C composite cell was also operated at a capacity of 0.5 mAh under oxygen atmosphere, and the charge / discharge curves showed significantly better coulombic efficiency (73%, dotted line in Figure 5) compared to the same cell assembled with an NMC cathode (described below as Comparative Example 1).
[0078] Coin-type cells were also assembled in a glove box filled with dry air. For this, the electrolyte was 0.2 M LiNO in DOL / DME. 3 , a mixture of 0.2 M LiBOB and 0.5 M LiTFSI. The experiment had a voltage cutoff condition from 2.0 to 3.5 V at 0.3 C, and the cyclability of the cell is plotted in Figure 7 (SS).
[0079] Example 2: An anode-free metal halide cell assembled with a LiI-carbon composite cathode and a Ni current collector was operated under dry air.
[0080] The same cell components and assembly method as described in the general procedure were applied, except that the current collector was Ni instead of SS. Using Ni current collector, 0.2 M LiNO in DOL / DME solution was used. 3Coin cells were assembled with an electrolyte containing 0.2 M LiBOB (lithium bis(oxalate)borate), and 0.5 M LiTFSI. The assembled cells were operated under a voltage cutoff condition of 2.0-3.5 V at 0.3 C. The charge-discharge curves and cyclability are plotted in Figure 9 and Figure 10 (Ni), respectively.
[0081] Example 3: An anode-free metal halide cell assembled with a LiI-carbon composite cathode and a PEG-POSS coated SS current collector was operated under oxygen.
[0082] The cells were assembled according to the general method described above. A cross-linked PEG-POSS (PEG:PEG-methyl ether acrylate, POSS: methacrylic cage silsesquioxane) film was applied onto the SS metal current collector as an artificial protective layer. The cross-linked coating process was carried out in an Ar-filled glove box. The PEG was freeze-dried under vacuum for 2 days and then stored on molecular sieves. PEG, POSS and photoinitiator (Darocur1173) were all mixed based on a 10:1 weight ratio as PEG:POSS and 0.1 wt% UV initiator of the total solution. After stirring the resulting solution for 10 min, the solution was applied onto the current collector by doctor blade coating and the coating layer was polymerized by UV exposure for up to 2 min.
[0083] For electrochemical testing and SEM analysis, the experiments were performed under oxygen atmosphere, so a Swagelok cell was assembled and purged with oxygen gas for 30 seconds. Initial cycle (FIG. 6) and long-term cycle (FIG. 7) tests were performed under a current of 0.5 mA for 30 minutes with a 0.25 mAh capacity cutoff. To observe the lithium deposition on the current collector, a cell with a PEG / POSS coated stainless steel current collector was assembled and charged to a capacity of 0.1 mAh. After cell disassembly, the POSS-PEG coated current collector was carefully rinsed with a DOL / DME solvent mixture and then dried under vacuum at room temperature. Cross-sectional SEM images of the POSS-PEG coated current collector are shown in FIG. 8A and FIG. 8B. Lithium was deposited directly on the SS current collector, under the POSS-PEG artificial SEI layer.
[0084] Example 4: An anode-free metal halide cell assembled with a LiI-carbon composite cathode and a PVA-coated SS current collector was operated under dry air.
[0085] An anode-free metal halide cell with a LiI / C composite cathode and a SS current collector was prepared using the general procedure described above. An artificial SEI layer of polyvinyl alcohol (PVA) polymer was coated onto the SS current collector. For this test, 5 wt% PVA in deionized water solution was applied to the SS current collector by doctor blade method. After drying in an oven at 60 °C for 12 h, the polymer-coated SS was used as the current collector. 0.2 M LiNO in DOL / DME solvent was added to the SS current collector. 3 Coin cells assembled with electrolytes having 0.1 M LiBOB, 0.2 M LiTFSI, and 0.5 M LiTFSI were operated at 0.3 C in dry air atmosphere, and the resulting cycle lives are plotted in Figure 10.
[0086] Example 5: An anode-free metal halide cell assembled with a LiI-carbon composite cathode and a PVA-coated Ni current collector was operated under dry air.
[0087] An anode-free metal halide cell with a LiI / C composite cathode and a Ni current collector was prepared by the general procedure described above. A PVA polymer coating was applied to the Ni current collector to form an artificial SEI layer. 0.2 M LiNO in DOL / DME solvent was added. 3 Coin cells with an electrolyte of 0.2 M LiBOB and 0.5 M LiTFSI were assembled in a glove box filled with dry air and operated at 0.3 C with a voltage cutoff of 2.0–3.5 V.
[0088] Comparative Example 1: An anode-free lithium-ion battery assembled with an NMC622 cathode was operated under oxygen.
[0089] For comparison, a conventional Li(Ni0.6Mn0.2Co0.2)O2 (NMC622) cathode, an electrode of 1M LiPF6 in EC / DEC (ethylene carbonate / diethyl carbonate), a Celgard® 2325 separator, and a SS current collector were obtained. The SS-NMC cell was assembled in a Swagelok cell configuration in an Ar-filled glove box. Before the charge / discharge test, oxygen gas was bubbled into the assembled cell for 30 s, and the cell started to operate under oxygen atmosphere after closing the inlet / outlet valves. The cell was filled to a capacity of 1 mAh to deposit lithium on the SS current collector, and the surface morphology of the deposited lithium was observed by scanning electron microscopy (SEM) after the SS substrate was rinsed with DMC solvent and dried in vacuum at room temperature for 1 h. As shown in Figure 4 (left panel), sharp needle-like structures are formed by lithium deposits (lithium dendrite growth), which eventually cause short circuits in the battery. As shown in Figure 5 (solid line), the cell operated at 0.5 mA for 1 hour exhibits poor coulombic efficiency (49%).
[0090] The terms used herein are merely for the purpose of describing particular embodiments and are not intended to be limitations of the various embodiments. As used herein, the singular forms "a", "an" and "the" are intended to include the plural unless the context expressly indicates otherwise. It will be further understood that the terms "comprise" and / or "comprising", when used herein, indicate the presence of stated features, integers, steps, operations, elements, or components or combinations thereof, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, or groups thereof, or combinations thereof. In the preceding detailed description of exemplary embodiments of the various embodiments, reference has been made to the accompanying drawings, in which like numbers represent like elements, which show, by way of illustration, specific exemplary embodiments in which the various embodiments may be practiced. These embodiments have been described in sufficient detail to enable those skilled in the art to practice the embodiments, but other embodiments may be used and logical, mechanical, electrical and other changes may be made without departing from the scope of the various embodiments. In the foregoing description, many specific details have been set forth to provide a thorough understanding of the various embodiments. However, the various embodiments may be practiced without these specific details. In other instances, well-known circuits, structures and techniques have not been shown in order not to obscure the embodiments.
[0091] As used herein, "multiple" when used in reference to an item means one or more of the items. For example, "multiple different types of networks" is one or more different types of networks.
[0092] Where different reference numerals include common numbers preceding different letters (e.g., 100a, 100b, 100c) or punctuation marks preceding different numbers (e.g., 100-1, 100-2 or 100.1, 100.2), use of the reference letter alone (e.g., 100) without a letter or following number may refer to the group of elements as a whole, any subset of the group, or an illustrative exemplar of the group.
[0093] Furthermore, the phrase "at least one of," when used with a list of items, means that different combinations of one or more of the listed items can be used, and only one of each item in the list may be required. In other words, "at least one of" means any combination of items, and while multiple items from the list may be used, not all items in the list are required. An item can be a particular object, thing, or category.
[0094] For example, but not limited to, "at least one of item A, item B, or item C" may include item A, item A and item B, or item B. This example may also include item A, item B, and item C, or item B and item C. Of course, any combination of these items may be present. In some example embodiments, "at least one of" can be, for example, but not limited to, two items A, one item B, ten items C, four items B and seven items C, or any other suitable combination.
[0095] In the foregoing, various embodiments have been referenced. However, it should be understood that this disclosure is not limited to the specifically described embodiments. Rather, any combination of the described features and elements, whether related to different embodiments or not, is contemplated for implementing and practicing the present disclosure. Many modifications, changes and variations will become apparent to those skilled in the art without departing from the scope of the described embodiments. Furthermore, the embodiments of the present disclosure may obtain advantages over other possible solutions or prior art, but whether or not a particular advantage is obtained by a given embodiment is not a limitation of the present disclosure. Thus, the described aspects, features, embodiments, and advantages are merely exemplary and are not considered elements or limitations of the appended claims unless expressly stated in the claims. In addition, it is intended that the following claims be construed to cover all such changes and modifications as falling within the scope of the invention.
[0096] Below, a non-limiting list of exemplary embodiments is provided to demonstrate certain aspects of the present disclosure.
[0097] Exemplary embodiment 1 is an anode-free metal halide battery that includes a negative current collector including a passivation layer of an electrically insulating material that allows metal ion migration, an electrolyte including an ionically conductive material, and a cathode including a metal halide salt incorporated into a conductive material, the electrolyte being in contact with the negative current collector and the cathode.
[0098] Exemplary embodiment 2 includes the anode-free metal halide battery of exemplary embodiment 1, with or without optional features. In this exemplary embodiment, the anode-free metal halide battery includes an oxidizing gas.
[0099] Exemplary embodiment 3 includes the anode-free metal halide battery of any one of exemplary embodiments 1 or 2, including or excluding an optional feature, in which a passivation layer is formed naturally on the negative current collector in contact with the electrolyte.
[0100] Exemplary embodiment 4 includes the anode-free metal halide battery of any one of exemplary embodiments 1 through 3, including or excluding optional features. In this exemplary embodiment, the conductive material is a porous carbon material and forms a metal halide-carbon composite cathode.
[0101] Exemplary embodiment 5 includes the anode-free metal halide battery of any one of exemplary embodiments 1 through 4, including or excluding optional features, in which the electrolyte is selected from the group consisting of a liquid electrolyte, a gel polymer electrolyte, a solid polymer electrolyte, a ceramic-based electrolyte, a polymer-ceramic composite electrolyte, and combinations thereof.
[0102] Exemplary embodiment 6 includes the anode-free metal halide battery of any one of exemplary embodiments 1-5, with or without optional features. In this exemplary embodiment, the passivation layer includes an artificially formed ionically conductive material. Optionally, the ionically conductive material is selected from the group consisting of linear polymers, crosslinked polymers, star polymers, block copolymers, metal oxides, and combinations thereof. Optionally, the ionically conductive material further includes an inorganic filler selected from the group consisting of carbon nanotubes, nanoparticles, polyhedral silsesquioxane (POSS) compounds, and combinations thereof.
[0103] Exemplary embodiment 7 includes the anode-free metal halide battery of any one of exemplary embodiments 1 through 6, including or excluding optional features. In this exemplary embodiment, the anode-free metal halide battery includes a non-conductive separator between the negative current collector and the cathode.
[0104] Exemplary embodiment 8 includes the anode-free metal halide battery of any one of exemplary embodiments 1 to 7, including or excluding optional features. In this exemplary embodiment, the thickness of the passivation layer ranges from 0.1 nanometers to 20 micrometers.
[0105] Exemplary embodiment 9 includes the anode-free metal halide battery of any one of exemplary embodiments 1 through 8, including or excluding optional features. In this exemplary embodiment, the thickness of the passivation layer is between 0.1 nanometers and 1 micrometer.
[0106] Exemplary embodiment 10 includes the anode-free metal halide battery of any one of exemplary embodiments 1 through 9, with or without optional features. In this exemplary embodiment, the negative current collector functions as the anode by having a metal deposited thereon.
[0107] Exemplary embodiment 11 includes the anode-free metal halide battery of any one of exemplary embodiments 1 through 10, including or excluding optional features. In this exemplary embodiment, the negative current collector is a metal foil disposed at the anode of the battery.
[0108] Exemplary embodiment 12 includes the anode-free metal halide battery of any one of exemplary embodiments 1 through 11, including or excluding optional features. In this exemplary embodiment, the anode-free metal halide battery includes a positive current collector.
[0109] Exemplary embodiment 13 is an anode-free metal halide battery that includes a negative current collector, an electrolyte including a solvent and at least one ionically conductive salt, and a cathode including a metal halide compound deposited on a conductive carbon material, the electrolyte being in contact with the negative current collector and the cathode.
[0110] Exemplary embodiment 14 includes the anode-free metal halide battery of exemplary embodiment 13, with or without optional features. In this exemplary embodiment, the cathode includes lithium ions deposited on a porous carbon material. Optionally, the porous carbon material is a LiI-carbon composite.
[0111] Exemplary embodiment 15 includes the anode-free metal halide battery of any one of exemplary embodiments 13-14, with or without optional features. In this exemplary embodiment, the passivation layer includes an artificially formed ionically conductive material. Optionally, the ionically conductive material is selected from the group consisting of polyvinyl alcohol (PVA) and poly(ethylene glycol) (PEG) copolymerized with polyhedral silsesquioxane (POSS).
[0112] Exemplary embodiment 16 includes the anode-free metal halide battery of any one of exemplary embodiments 13 to 15, including or excluding optional features. In this exemplary embodiment, the anode-free metal halide battery includes a separator between the negative current collector and the cathode.
[0113] Exemplary embodiment 17 includes the anode-free metal halide battery of any one of exemplary embodiments 13 to 16, including or excluding optional features. In this exemplary embodiment, the thickness of the passivation layer ranges from 0.1 nanometers to 20 micrometers.
[0114] Exemplary embodiment 18 is a method for forming an anode-free metal halide battery. The method includes forming a metal halide battery cell, the metal halide battery cell including a negative current collector and not including a separate anode. The method further includes applying a charging voltage to the metal halide battery cell to reduce metal ions to the corresponding metal on the negative current collector.
[0115] Exemplary embodiment 19 includes the method of exemplary embodiment 18 with or without optional features. In this exemplary embodiment, the metal halide battery cell further includes a passivation layer on the top side of the negative current collector, an electrolyte including a solvent and at least one ion-conducting salt, and a cathode including a metal halide compound deposited on a conductive material, the electrolyte being in contact with the negative current collector and the cathode. Optionally, the passivation layer includes an artificially formed ion-conducting material selected from the group consisting of polyvinyl alcohol (PVA) and poly(ethylene glycol) (PEG) copolymerized with polyhedral silsesquioxane (POSS). Optionally, the cathode includes lithium iodide deposited on a porous carbon material, and by applying a charging voltage to the battery cell, lithium ions released from the cathode are reduced to lithium metal on the negative current collector.
Claims
1. 1. An anode-free metal halide battery comprising: a negative current collector including a passivation layer of an electrically insulating material that allows migration of metal ions; an electrolyte including an ion-conducting material; a cathode comprising a metal halide salt incorporated in a conductive material; wherein the electrolyte is in contact with the negative current collector and the cathode.
2. 10. The battery of claim 1 further comprising an oxidizing gas.
3. 2. The battery of claim 1, wherein the passivation layer forms spontaneously on the negative current collector in contact with the electrolyte.
4. 10. The battery of claim 1, wherein the conductive material is a porous carbon material forming a metal halide-carbon composite cathode.
5. 2. The battery of claim 1, wherein the electrolyte is selected from the group consisting of liquid electrolytes, gel polymer electrolytes, solid polymer electrolytes, ceramic-based electrolytes, polymer-ceramic composite electrolytes, and combinations thereof.
6. 10. The battery of claim 1, wherein the passivation layer comprises an artificially formed ionically conductive material.
7. 7. The battery of claim 6, wherein the ionically conductive material is selected from the group consisting of linear polymers, crosslinked polymers, star polymers, block copolymers, metal oxides, and combinations thereof.
8. 7. The battery of claim 6, wherein the ionically conductive material further comprises an inorganic filler selected from the group consisting of carbon nanotubes, nanoparticles, polyhedral silsesquioxane (POSS) compounds, and combinations thereof.
9. 10. The battery of claim 1 further comprising a non-conductive separator between said negative mass and said cathode.
10. 10. The battery of claim 1, wherein the passivation layer has a thickness in the range of 0.1 nanometers to 20 micrometers.
11. 2. The battery of claim 1, wherein the passivation layer has a thickness of from 0.1 nanometers to 1 micrometer.
12. 10. The battery of claim 1, wherein the negative current collector functions as an anode by having a metal deposited thereon.
13. 10. The battery of claim 1, wherein the negative current collector is a metal foil disposed in the anode of the battery.
14. 10. The battery of claim 1 further comprising a positive current collector.
15. 1. An anode-free metal halide battery comprising: A negative current collector; an electrolyte comprising a solvent and at least one ionically conductive salt; a cathode comprising a metal halide compound deposited on a conductive carbon material; wherein the electrolyte is in contact with the negative current collector and the cathode.
16. 16. The battery of claim 15, wherein the cathode comprises lithium ions deposited on a porous carbon material.
17. The battery of claim 16, wherein the porous carbon material is a LiI-carbon composite.
18. 16. The battery of claim 15, wherein the passivation layer comprises an artificially formed ionically conductive material.
19. The ion-conducting material is Polyvinyl alcohol (PVA), Poly(ethylene glycol) (PEG) copolymerized with polyhedral silsesquioxane (POSS); Poly(ethylene glycol), Poly(propylene glycol), Polycarbonate, polyester, Polyethylene oxide (PEO), Polyurethane (PU), Styrene butadiene rubber (SBR), Polyvinylidene fluoride (PVDF), and 20. The battery of claim 18, wherein the polymer is selected from the group consisting of poly(tetrafluoroethylene) (PTFE).
20. 16. The battery of claim 15, further comprising a separator between the negative current collector and the cathode.
21. 16. The battery of claim 15, wherein the passivation layer has a thickness in the range of 0.1 nanometers to 20 micrometers.
22. 1. A method for forming an anode-free metal halide battery, comprising: forming a metal halide battery cell, the metal halide battery cell including a negative current collector and not including a separate anode; applying a charging voltage to the metal halide battery cell to reduce metal ions to their corresponding metals on the negative current collector; A method comprising:
23. The metal halide battery cell comprises: a passivation layer on the negative current collector; and an electrolyte comprising a solvent and at least one ionically conductive salt; a cathode comprising a metal halide deposited on a conductive material; Including, the electrolyte is in contact with the negative current collector and the cathode; 23. The method of claim 22.
24. The passivation layer comprises: Polyvinyl alcohol (PVA), Poly(ethylene glycol) (PEG) copolymerized with polyhedral silsesquioxane (POSS); Poly(ethylene glycol), Poly(propylene glycol), Polycarbonate, polyester, Polyethylene oxide (PEO), Polyurethane (PU), Styrene butadiene rubber (SBR), Polyvinylidene fluoride (PVDF), and 24. The method of claim 23, comprising an artificially formed ionically conductive material selected from the group consisting of poly(tetrafluoroethylene) (PTFE).
25. 24. The method of claim 23, wherein the cathode comprises lithium iodide deposited on a porous carbon material, and application of the charging voltage to the battery cell reduces lithium ions released from the cathode to lithium metal on the negative current collector.
Citation Information
Patent Citations
Positive electrode active material, battery using the positive electrode active material, and manufacture of battery
JP1998003924A
Composite solid electrolyte, protection negative electrode including the same, lithium battery, and method for manufacturing composite solid electrolyte
JP2017191766A
Lithium secondary battery
JP2019537226A
Lithium secondary battery
JP2020510292A
Lithium secondary battery
JP2020524889A